(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Background: Numerous studies have been conducted to examine the growth factors capable of exerting simultaneous effects on the vascular and metabolic components of the pathogenesis of diabetic retinopathy (DR). Purpose: To examine tear and serum brain-derived neurotrophic factor (BDNF) levels in type 2 diabetes mellitus (DM2) patients with and without DR. Material and Methods: One hundred and seventy patients with DM2 and 84 practically healthy individuals without any eye disease (totally, 254 individuals and 504 eyes) were included in the study. Of the total individuals included in the study, 49.2% were males and 50.8% were females. The mean age plus or minus standard deviation was 67 ± 4.2 years for men and 64 ± 5.6 years for women. Results: It was found that tear BDNF levels lower than 97.5 pg/ml and serum BDNF levels lower than 23.8 ng/ml indicate the transition to DR, whereas tear BDNF levels lower than 62.0 pg/ml and serum BDNF levels lower than 12.0 ng/ml indicate the development of proliferative DR. Conclusion: Mean serum BDNF levels as low as below 23.8 ± 1.33 ng/ml and mean tear BDNF levels as low as below 97.5 ± 5.57 pg/ml are an early sign of DR.